Microhole Forming and Creep Behavior of Fe‐Based Nanocrystalline Alloys under Laser Dynamic Impact. Issue 5 (24th February 2020) - Liu, Huixia; Cui, Jiankun; Wang, Lei; Ma, Youjuan; Wang, Xiao
Abstract : Given the difficulty of forming Fe‐based nanocrystalline alloys at room temperature, this study uses soft film as a flexible micropunch to realize the formation of microholes in Fe‐based nanocrystalline alloy foil under laser impact. The effect of laser energy and soft film thickness on forming accuracy of the workpiece is studied, particularly fracture surface characteristic of the workpiece and the creep behavior of the workpiece. It is found that with increased laser energy, forming accuracy is improved. The fracture surface comprises sliding and fracture regions, and a large number of melt droplets and melt zone are distributed on the surface of the fracture region. This feature indicates that the workpiece exhibits brittle fracture in macroscopic scale and exhibits plastic fracture in the microscopic scale. The creep behavior of the workpiece comprises transient creep and steady state creep. With the extension of creep time, the stress exponent reaches a stable state. With the increase in load, the stress exponent also increases, which shows the obvious maximum load dependence. Abstract : Compared with the soft film thickness, the improvement of laser energy is more conducive to the improvement of forming accuracy. Under high‐speed laser impact, the Fe‐based nanocrystalline alloy foil has both brittle and ductile fracture characteristics. Laser impact has neither changed the structural characteristics of materials nor the mechanical properties of materials.